Metformin loaded porous particles with bio-microenvironment responsiveness for promoting tumor immunotherapy. (21st January 2021) - Wen, Yuanyuan; Liu, Yuxiao; Chen, Canwen; Chi, Junjie; Zhong, Liping; Zhao, Yongxiang; Zhao, Yuanjin
Abstract : This article presented a novel tumor-microenvironment-responsive particles delivery system with metformin-loaded chitosan inverse opal core and manganese dioxide shell for inhibiting PD-1/PD-L1 signaling pathway and promoting tumor immunotherapy. Abstract : PD1/PD-L1 antibody blockade-based immunotherapy has been widely recognized in the field of cancer treatment; however, only a small number of cancer patients have been shown to respond well due to the PD1/PD-L1 antibody hydrolysis induced substandard immunotherapeutic efficacy and the low immunogenicity and immunosuppressive tumor microenvironment of the patients. Here, we present a novel tumor microenvironment (TME) responsive particle delivery system with a metformin-loaded chitosan (CS) inverse opal core and a manganese dioxide (MnO2 ) shell (denoted as CS-metformin@MnO2 particles) for inhibiting the PD-1/PD-L1 signaling pathway and promoting tumor immunotherapy. Benefiting from the interconnected porous structure of the inverse opal, metformin can be easily extensively loaded into the CS particles. With the coating of the TME responsive MnO2 shells, the particle delivery system was imparted with an intelligent "trigger" to prevent premature leaking of the drug until it reaches the tumor tissue. We have demonstrated that CS-metformin@MnO2 particles were able to promote the apoptosis of tumor cells through immunotherapeutic means both in vivo and in vitro . Specifically, the viability of tumor cells in the drug carrier-treated group was nearly 20% less than in the untreated group. In addition, the CS particles could serve as scaffolds for the regeneration of normal tissues and promote post-surgical wound healing due to their biocompatibility and antibacterial ability. These results make CS-metformin@MnO2 particles an excellent delivery system in tumor immunotherapy and post-surgical wound healing applications.